Handbook of research on computational methodologies in gene regulatory networks - Caragea, Doina; Das, Sanjoy , 1968-; Hsu, William H. , 1973-; Welch, S. M. [ (Stephen M.)] (Medical Information Science Reference, 2010)
"This book focuses on methods widely used in modeling gene networks including structure discovery, learning, and optimization"--Provided by publisher.